PENGARUH PENERAPAN MODEL PEMBELAJARAN INOVATIF TIPE EXAMPLES NON EXAMPLES TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI SMA NEGERI 1 TEMBILAHAN HULU RIAU - Putri, Dwy Puspita (STKIP PGRI Sumbar, 2014)
This research is motivated by low yields studying biology class XI student of SMA Negeri 1 Tembilahan Hulu in Riau on Human Reproductive System materials in the school year 2012/2013. One way that teachers can be applied to solve the problem is to implement innovative learning model examples non examples are not expected to improve student learning outcomes. This study aims to determine the effect of the type of innovative learning model examples non examples of learning outcomes biology class XI SMA 1 Tembilahan Hulu in Riau. This study is an experimental research and the study design was a Randomized Control Group Posttest Only Design, sampling technique was purposive sampling. The results of the study can be seen that the experimental class had an average higher than the control class where t_hitung > t_tabel which Hâ research hypothesis is accepted, it can be concluded that the application of innovative learning model of type examples non examples to improve learning outcomes biology class XI SMA 1 Hulu Tembilahan Riau.